Climate-change induced human migration and socio-political changes in eastern India during the Meghalayan age - Sengupta, Dipanwita; Dutt, Som; Warken, Sophie F.; Singam, Arvinash; Frank, Norbert; Sagwal, Sumit; Maurya, Sakshi (Palaeogeography, palaeoclimatology, palaeoecology, 2025)
The Holocene climate records, available from the Indian subcontinent are in fragments, majority having low temporal resolution and illustrate regional variability in proxy response. The impact of climate fluctuations on contemporary societies has been discussed in general. However, region specific climate-cultural linkages have not been adequately represented. This study presents a four-millennia-long time-series of Indian Summer Monsoon (ISM) variability from northeastern India using a U-Th dated stalagmite δ18O time series, particularly emphasising on the human development in eastern and northeastern India. The record exhibits ISM variability during ∼5.5 to ∼1.0 kyr BP. The results indicate weakened ISM conditions during 4.2-4.0 kyr BP and strong phases during 2.74-2.39 kyr BP and 1.42-0.97 kyr BP. The ISM fluctuations over the studied period had been significantly influenced by changes in the North Atlantic Oscillations (NAO), Intertropical Convergence Zone (ITCZ) latitudinal positioning and solar activity through teleconnections. Anthropological, historical and paleoclimatological evidences stitched together elucidate a story of climate induced human development in eastern and northeastern India. Signs of prosperous urban centres were evident in eastern India by ∼2.8 kyr BP and large kingdoms in this region established and rose to power between ∼1.3-0.9 kyr BP, mainly during the moderate to high ISM conditions.